2017
DOI: 10.21276/aimdr.2018.4.1.sg15
|View full text |Cite
|
Sign up to set email alerts
|

Retzius Space: Not A Single Anatomical Entity: New Insights, Simplified & Illustrated in A Laparoscopic Study during TEPP Hernioplasty for Inguinal Hernia

Abstract: Background: Casual internet surfing at times proves extremely rewarding with astonishing results. Chance finding of an unknown old PhD thesis prompted documentation of detailed description of retropubic spaces supplementary to the author's recent publication (Ansari MM. Ann Int Med Den Res 2017; 3(5): SG25-31.). Methods: Prospective study in adult patients with inguinal hernia who underwent laparoscopic total extra-peritoneal preperitoneal (TEPP) hernioplasty through standard 3-midline-port technique at J. N. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…In his research study, Ansari observed multiple potential spaces in the retropubic region. He concluded that the Retzius space needs to be re-evaluated and re-defined for anatomist and practicing surgeons [32]. We totally agree with Ansari, as in the retropubic region, there are fascial layers and spaces, which have not been mentioned in anatomical textbooks or during surgical dissection.…”
Section: Retropubic (Retzius) Spacesupporting
confidence: 65%
See 2 more Smart Citations
“…In his research study, Ansari observed multiple potential spaces in the retropubic region. He concluded that the Retzius space needs to be re-evaluated and re-defined for anatomist and practicing surgeons [32]. We totally agree with Ansari, as in the retropubic region, there are fascial layers and spaces, which have not been mentioned in anatomical textbooks or during surgical dissection.…”
Section: Retropubic (Retzius) Spacesupporting
confidence: 65%
“…The urachus (median umbilical ligament) lies on the inner aspect of the anterior abdominal wall dorsal to the fascial layers (umbilical vesical fascia, umbilical prevesical fascia, transversalis fascia). The urachus and both medial umbilical ligaments are used as landmarks, just above the bladder dome, as the site for the peritoneal incision [31,32]. After cutting the median umbilical ligament, dissection proceeds in the ventro-lateral direction up to the retropubic space boundaries.…”
Section: Retropubic (Retzius) Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Posterior rectus canal, currently the most preferred approach for the laparoscopic total extraperitoneal preperitoneal (TEPP) hernioplasty for the inguinal hernia, is traditionally taught to be bounded anteriorly by the fleshy rectus abdominis muscle and bounded posteriorly by the incomplete aponeurotic posterior rectus sheath in up-per part and the transversalis fascia in the lower part. Under excellent lighting and magnification of modern laparoscopy, not only new structures/tissue planes and phenomena have been discovered (2,4,8,9,(11)(12)(13)(14)(15)(16)(17)(23)(24)(25), but also the frequent anatomic variations often reported in the previous cadaveric studies were confirmed (7,(26)(27)(28)(29)(30)(31), which are visualized too clearly to refute even against the prior fixed mindset based on the traditional anatomy classroom teaching (2), although they rarely received the attention of the authors of the traditional textbooks of surgery &/or anatomy commonly read by the medical students. Current bilaminar/trilaminar concept of the posterior rectus sheath in cadaveric studies (27,30,32) is supported by the laparoscopic live anatomical findings of double-/multi-layered posterior rectus sheath ( Figure 15) (9,23).…”
Section: Discussionmentioning
confidence: 99%
“…Последними исследованиями было доказано наличие нескольких фасциальных слоев внутри пространства Ретциуса, поэтому не совсем верно считать его единым анатомическим образованием [29]. Вдоль передней поверхности мочевого пузыря к пупку тянется пузырнопупочная или предпузырная фасция [9].…”
Section: результаты исследования и их обсуждениеunclassified